The voice in the headphones - Grubbs, David, 1967- (Duke University Press, 2020)
"THE VOICE IN THE HEADPHONES is a book-length poem, largely but not exclusively in prose. Following in form Grubbs's previous book, Now the Audience is Assembled, which was about a musical performance, this book takes the reader into the recording booth. The poem takes place within the recording studio and Grubbs's fictional band, The Familiar Faces, surfaces and disappears throughout the text as the poems cycle through the creative process of music making and recording. The basic unit of each piece is the page, and the book presents itself in a hybridized form, recontextualizing contemporary poetry, using the language of recording in the studio as the material for the poem. The book is one continuous poem, flowing and looping through the forms and cycles of a studio recording session. Grubbs describes the process of recording as well as the emotions, tools, and systems that undergird music making. The past arrives in the musician's headphones, and the voice mixes with creativity in a series of loops. The poem loops in and on itself, in a way reminiscent of a record or a CD, returning to the present and to the beat. Grubbs describes his influences and inspirations. The Familiar Faces, his band, recur throughout the book within the lines of each page, which are a metaphor for the studio and the music venue. The reader follows Grubbs's creative journey through double takes. The lines rise and fall with the crescendo of the studio. The book is the rehearsal space, and the music is in each new line. This book will be of interest to music scholars and students, readers of the avant-garde arts, and creative writers"--